Docking investigation of Thevetia peruviana plant compounds for targeting molluscicidal activity against Biomphalaria alexandrina snails, the intermediate host of Schistosoma mansoni - Samah I. Ghoname; Basma H. Amin; Asmaa T. Mohamed; Olfat A. Hammam; Hebat-Allah A. Dokmak (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Thevetia peruviana, commonly known as Yellow Oleander or Cabbage Tree, is a tropical shrub. Extracts from various parts of the plant (e.g., leaves, seeds) have demonstrated pesticidal properties, including the ability to repel or kill intermediate hosts of Schistosomiasis. Methods This study employed gas chromatography–mass spectrometry (GC–MS) analysis to identify 33 components in the ethanol extract, with key compounds exhibiting antioxidant, anti-inflammatory, anticancer, and antimicrobial properties. Additionally, the research investigated the molluscicidal activity of the plant extract, its impact on Caspase-3 expression, steroid sex hormone levels in Biomphalaria alexandrina, and histological alterations in the digestive and hermaphrodite glands. Levels of nitric oxide and comet assay results were evaluated in Schistosoma mansoni-Infected B. alexandrina snails, comparing them to a control group at the first cercarial shedding stage. The analysis of docking scores provides a quantitative measure of binding affinity, where more negative values indicate stronger interactions. The variation in docking scores highlights the diverse binding potentials of these compounds and emphasizes the importance of considering specific molecular interactions in the context of Caspase-3 modulation. Results The study identified 33 components in the ethanol extract of T. peruviana, analyzed by GC–MS. Molluscicidal tests demonstrated concentration-dependent sensitivity, with an LC90 value of 43.79 ppm. Caspase-3 expression was upregulated in B. alexandrina snails following treatment with LC10 ppm and LC25 ppm, affecting steroid sex hormone levels. Histological analysis revealed significant damage to the digestive and hermaphrodite glands, indicating reproductive disturbances post-treatment. At the first cercarial shedding stage, nitric oxide levels increased at LC10 ppm and LC25 ppm compared to the control group (P < 0.001). DNA damage percentage also increased with higher treatment concentrations, showing varied responses in S. mansoni-infected B. alexandrina snails. The in silico study identified Glycan Sialylated Tetraose Type-2 as the most active compound, exhibiting the highest affinity and the most significant effect against Caspase-3. Conclusions Thevetia peruviana extract exhibited concentration-dependent molluscicidal effects on B. alexandrina snails, impacting key biological processes, such as Caspase-3 expression and sex hormone levels. Histological analysis revealed glandular damage, while increased nitric oxide levels and DNA damage highlighted the extract’s effects on infected snails. Furthermore, the findings emphasize the importance of understanding ligand–protein interactions, providing valuable insights into targeting apoptosis through Caspase-3 modulation to control the intermediate host of S. mansoni.